The relationship between polymorphisms of microRNA and preeclampsia: A protocol for meta-analysis and bioinformatics prediction. Issue 14 (9th April 2021) - Li, Tao; Chen, Yihong; Lai, Yi; He, Guoqian; He, Guolin
Abstract: Background: Preeclampsia has genetic correlation. Many studies have shown that microRNA (miRNA) polymorphism is highly associated with preeclampsia, but the results are inconsistent. The purpose of this study is to systematically evaluate the relationship between miRNA polymorphism and preeclampsia. Methods: In this study, the search time is set from the establishment of the database on January 2021. The search database include China National Knowledge Infrastructure (CNKI), Wanfang, VIP and China Biology Medicine disc (CBM), PubMed, EMBASE, and Web of Science, and the Cochrane Library. The subjects are case-control studies on the relationship between miRNA polymorphism and preeclampsia. The language is limited to English and Chinese. The data of the included study are extracted and the literature quality is evaluated by 2 researchers independently. The data are statistically analyzed through Stata 16.0 software. We also predicted the miRNA secondary structure and the binding sites of miRNA interaction with its target genes Results: This review will be disseminated in print by peer-review. Conclusion: This study will provide evidence-based medicine to elucidate the genetic tendency of preeclampsia. Ethics and dissemination: Private information from individuals will not be published. This systematic review also does not involve endangering participant rights. Ethical approval will not be required. The results may be published in a peer-reviewed journal or disseminated at relevant conferences. OSF Registration number: DOI 10.17605/OSF.IO/MJY2X.